(untitled) (Revista de História da UEG (REVHIST), 2024)
The Tale of Bygone Years (in original Повѣсти времѧньных лѣт, Poviest vremennykh liet), also called Nestor’s Chronicle because it has long been considered the work of Nestor of Pecherska, was written around 1116 in the Slavonic or Paleo-Slavic language and is the oldest chronicle of Kievan Rus, the oldest East Slavic state. It covers a time span from 850 to 1110, and for this reason represents a primary source of information on the history of Eastern Europe in the Middle Ages, especially for the history of Russia, Belarus and Ukraine. This literary monument of so-called Kievan Rus’ was illustrated with numerous miniatures in the Radziwiłł Code, a manuscript presumably dating from the beginning of the 13th century, preserved in two copies from the 15th century. It is the only surviving medieval illuminated chronicle, and its illustrations, by being constantly replicated over the last century, have formed that distinctive set of images that one tends to associate with the Kiev Rus’. The codex is believed to date from the early 1490s and is believed to be a copy of a lost illuminated manuscript from the 13th century. In these pages, we will check the adherence of the illustrations of the Radziwiłł Code and the manuscript of the Tale of Bygone Years, comparing the written pages and the iconographic choices in the illuminations. Keywords: Medieval art. Medieval Russian literature. Tale of Bygone Years. Radziwiłł Code. Illuminations.